Buccal dorsal augmentation ureteroplasty for extended ureteral stricture having an obliteration site - A. A. Volkov; I. D. Mustapaev; Z. A. Mirzaev; A. V. Muziev (Вестник урологии, 2025)
Buccal ureteroplasty is a surgery that is now increasingly encountered in urological practice. There are various techniques for performing this surgical procedure, which require further improvement. This article presents a clinical case and the immediate results of ureteroplasty utilising the oral mucosa via the augmentation anastomosis technique in a 40-year-old patient with an extended recurrent ureteral stricture having an obliteration site.